2021
DOI: 10.3389/fmicb.2021.671395
|View full text |Cite
|
Sign up to set email alerts
|

The Altitude of Coffee Cultivation Causes Shifts in the Microbial Community Assembly and Biochemical Compounds in Natural Induced Anaerobic Fermentations

Abstract: Coffee harvested in the Caparaó region (Minas Gerais, Brazil) is associated with high-quality coffee beans resulting in high-quality beverages. We characterize, microbiologically and chemically, fermented coffees from different altitudes through target NGS, chromatography, and conventional chemical assays. The genera Gluconobacter and Weissella were dominant in coffee’s fruits from altitudes 800 and 1,000 m. Among the Eukaryotic community, yeasts were the most dominant in all altitudes. The most dominant funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…These results show a variation in the chemical composition of the coffee in the function of the planting altitude. Other studies have also shown signi cant differences in the chemical composition of the coffees produced at different planting altitudes (Avelino et al 2005 andMartinez et al 2021;Pereira et al 2021). The concentration of acetic acid was greater in coffees produced at an altitude of 1,200 m than in the samples from the lowest altitudes (Martinez et al 2021).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These results show a variation in the chemical composition of the coffee in the function of the planting altitude. Other studies have also shown signi cant differences in the chemical composition of the coffees produced at different planting altitudes (Avelino et al 2005 andMartinez et al 2021;Pereira et al 2021). The concentration of acetic acid was greater in coffees produced at an altitude of 1,200 m than in the samples from the lowest altitudes (Martinez et al 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have also shown signi cant differences in the chemical composition of the coffees produced at different planting altitudes (Avelino et al 2005 andMartinez et al 2021;Pereira et al 2021). The concentration of acetic acid was greater in coffees produced at an altitude of 1,200 m than in the samples from the lowest altitudes (Martinez et al 2021). Furthermore, according to Pereira et al (2021), coffees produced in altitudes of 300 to 600 m have about 30 volatile compounds.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These authors performed the volatile extractions in coffee beans fermented by dry method and roasted using solid-phase microextraction method, and the volatile compounds were identified by gas chromatography combined with mass spectrometry (GC-MS). Using these analytic methods, Martinez et al (2021) observed about 60 volatile compounds in the coffee fruits produced at an altitude between 800 and 1000 m and fermented by spontaneous fermentation during 48 h. In 12 different cultivars of roasted C. arabica, 43 volatile compounds were identified using nuclear magnetic resonance and GC-MS (Wang et al, 2021). The coffee samples of these authors were obtained in five countries (Brazil, Colombia, Kenyan, Portugal, and Timor-Leste) that show different volatile compositions in coffee beans.…”
Section: Volatile Constituents Of Genotypesmentioning
confidence: 99%
“…This fermentation is affected by the processing of coffee cherries (Pereira et al 2020), the genetic variety of the plant (Bertrand et al 2006), and natural coffee microbiota (De Bruyn et al 2017). Another trend argues that coffee quality can be optimized with the application of microorganism's starters that modify the taste and texture (Bressani et al 2021;Evangelista et al 2015;Martinez et al 2021;Pereira et al 2017;Pereira et al 2021;Tang et al 2021). Moreover, the production of specialty coffees has suffered a profound revision in the form of processing, through the understanding and introduction of fermentation techniques, focusing on the observation of how chemical compounds interact with sensory pro les of the coffee drink (Avelino et al 2015;Brioschi Junior et al 2021;Pereira et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%